A Coordination Mechanism of Supply Chain with a Retailer and Two Competitive Suppliers. (31st May 2020) - Liu, Zhi-yang; Liu, Yong; Li, Hui
Abstract : To deal with coordination problem of a supply chain consisting of two competitive suppliers and a dominant retailer, considering these factors such as cooperation effort degrees and competition on the supply chain members, we establish a two-stage model considering cooperation effort degrees and competition of the suppliers from the perspectives of decentralized decision and centralized decision and exploit it to discuss the optional decisions and explore the impact of cooperation effort degrees on the profits of supply chain members. Then, we use a group negotiation model to establish a coordination mechanism. The results reveal that the decision variables and overall profit of the supply chain of suppliers and retailers under centralized decisions are better than those under the decentralized decisions. Besides, the degree of competition and price sensitivity have positive and negative effects on the efforts of suppliers and retailers, respectively. Meanwhile, the degree of cooperation between suppliers and retailers affects the profits of supply chain members and the whole supply chain in different degrees. Finally, the proposed value-added profit distribution mechanism can effectively deal with conflict problem and guarantee supply chain members and supply chain to maximize their profits and adopt the centralized decision.